Cumby, Art. A video clip on the use of water tanks in Heart's Content. Cumby, Art - Wilson, Lisa (2013)
Art Cumby talks about when Heart's Content once relied on water tanks for their water supply and how they had one put back in the town center as a fountain. In the accompanying photo, Patsy Piercy shows a hooked rug she is working on that depicts a water tank.